Analysis of the Form and Impact of the Implementation of Rsi Yajna on the Holy Day of Siwaratri in Mataram City - Ni Ketut Windhi Maretha; I Gusti Ngurah Sudiana; I Nyoman Subagia (Jayapangus Press, 2026)
Siwaratri Day is also celebrated with the Rsi Yajna ceremony by Hindus in Mataram City. This was done by visiting Sulinggih’s residence and giving sincere offerings. This is a form of respect for the role of sulinggih in the implementation of Hindu religious rites. However, most Hindus are only familiar with the mediksa ceremony as a form of implementing the Rsi Yajna. The purpose of this study is to explore the form and impact of implementing Rsi Yajna in Mataram City. Qualitative research design, with the Grounded Theory approach, is a method in the study process where data are collected through observation, interviews, and document analysis techniques. Data analysis is carried out in several stages, namely reduction, data display, and data verification, to ensure that there is no bias, as well as the use of triangulation techniques. Referring to the field findings, the implementation of Rsi Yajna was carried out by visiting the residences of the sulinggih, offering sedanas and punia, and also conducting joint worship at Griya, the sulinggih’s residence. In general, the impact of implementing the Rsi Yajna is classified into four domains: social, cultural, economic, and spiritual. Specifically, the increase in sradha and devotion is the most noticeable impact among Hindus. Therefore, the implementation of Rsi Yajna represents gratitude and aims to enhance the spiritual quality of Hindus in Mataram City. Through this study, it is hoped that it will provide an overview of the importance of Rsi Yajna among Hindus and serve as a literature review for future relevant studies.